Digital Trends of Social Religious Humanities: Understanding Discourse on Religious Moderation, Pancasila and Citizenship Education in Indonesia - Choirul Mahfud; Muyasaroh Muyasaroh; Ratna Rintaningrum; Niken Prasetyawati; Dyah S.Y Agustin; Ni Wayan Suarmini; Moh. Saifulloh; Syahraini Tambak; Ika Yunia Fauzia; Ahmad Munjin Nasih (MODELING: Jurnal Program Studi PGMI, 2022)
Indonesia is facing the digitalization era. It is making it possible to see opportunities for digitalization trends in the social, religious, and humanities. Not many are aware of this aspect which also influences the development and changes that occur in social, religious, and national life. From year to year, aspects of technology and humanities social interactions have increasingly important influences. This research is based on data, qualitative research approaches, and methods supported by digital or internet documentation sources. The essence of this research discussion is about how the social digitization trend of religion and humanities, especially in the discourse of religious moderation, Pancasila, and civic education. What is the impact of digitalization on the behavior of the community (netizens) in supporting the creation of good life order? Found several facts that cannot underestimate digital trends in the social humanities field. His contribution is extraordinary in influencing the behavior and knowledge of the people in Indonesia. Its impact is also felt in social innovation, humanities, and civic education today and in the future.